Human Cytomegalovirus Protein Expression Is Correlated with Shorter Overall Survival in Breast Cancer Patients: A Cohort Study - Touma Joel; Pantalone Mattia Russel; Rahbar Afsar; Liu Yan; Vetvik Katja; Sauer Torill; Söderberg-Naucler Cecilia; Geisler Jürgen (MDPI, 2025)
Background: Human cytomegalovirus (HCMV) is increasingly suggested to be involved in human carcinogenesis and onco-modulation due to its ability to contribute to all hallmarks of cancer. Growing evidence demonstrates a link between HCMV infection and various malignancies, including breast cancer, which incidence and mortality are still on the rise. The etiology of breast cancer remains mostly unclear, leaving 80% of breast cancer cases considered to be sporadic. Identifying novel risk- and prognostic factors for improved breast cancer treatment and increased survival rates, were the objectives of this study.
Methods: Automated immunohistochemical staining results for HCMV proteins in 109 breast tumors and lymph node metastasis were correlated with clinical follow-up data (>10 years). Statistical analyses for median Overall Survival (OS) were performed.
Results: Survival analyses revealed shorter median OS for patients with HCMV-IE positive tumors of 118.4 months compared to 202.4 months for HCMV-IE negative tumors. A higher number of HCMV-LA positive cells in the tumors was also associated with a shorter OS in patients (146.2 months vs. 151.5 months).
Conclusions: Our findings suggest a link between HCMV-infections and breast cancer prognosis, which paves the way for potential novel clinical intervention and targeted therapy that may prolong the overall survival of selected patients with breast cancer.